MEASURING PROFESSIONALISM IN POSTGRADUATE PAEDIATRIC RESIDENTS USING PROFESSIONALISM MINI-EVALUATION EXERCISE (P-MEX) - Asma Razzaq (Army Medical College Rawalpindi, 2019)
Objective: To measure professionalism in postgraduate Paediatric residents using P-MEX.